Autism identification across ethnic groups: a narrative review. Issue 3 (30th June 2020) - Tromans, Samuel; Chester, Verity; Gemegah, Eli; Roberts, Kristian; Morgan, Zoe; Yao, Guiqing Lily; Brugha, Traolach
Abstract : Purpose: The purpose of the paper is to review autism identification across different ethnic groups. Diagnosis of autism may be missed or delayed in certain ethnic groups, leading to such groups being underserved relative to their needs. This can result in members of such groups being effectively denied essential avenues of support that can substantially improve the quality of life of autistic persons as well as those whom care for them. Design/methodology/approach: A literature search for articles reporting autism identification across ethnic groups was undertaken. Data are compared, with a special focus on possible explanations for any inter-group variation. Findings: Autism identification appears to be generally lower in minority ethnic groups relative to the majority population. Individuals presenting with autism from minority groups appear to have more severe forms of the condition. Originality/value: There are a multitude of potential explanations for inter-ethnicity variation in autism identification, including health care-related factors, broader environmental influences, cultural factors and possible biological differences. Implications for clinical practice and public health include a need to look at means of ensuring equitable access to relevant autism diagnostic and support services across ethnic groups. Further work is required to better understand the belief systems that operate within specific ethnic groups, how this may potentially impact upon autism identification and measures to address the concerns of such groups.